Copyright Protection for Digital Content on Social Media in Indonesia (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The rapid expansion of social media has transformed the creation, distribution, and commercialization of digital content, generating new challenges for copyright protection in Indonesia. This study examines the adequacy of Indonesian copyright law in addressing the evolving dynamics of digital content circulation within platform based environments. Employing a non empirical normative legal research design, the study integrates statutory, conceptual, and case approaches to analyze legal materials, regulatory frameworks, judicial reasoning, and contemporary scholarly discourse. The findings indicate that Indonesian copyright law provides a substantial normative foundation for recognizing ownership, economic rights, and moral rights of digital creators. Nevertheless, significant enforcement obstacles persist due to technological acceleration, platform mediated dissemination, digital anonymity, cross border activities, and limited public awareness. The analysis further reveals a regulatory gap between formal legal protection and practical enforcement effectiveness. To address these challenges, the study proposes an adaptive copyright protection model that combines Digital Rights Management, automated detection technologies, strengthened platform accountability, digital literacy initiatives, coordinated institutional enforcement, and international legal cooperation. This integrated framework offers a forward looking strategy for enhancing copyright governance and ensuring sustainable protection of digital creativity in Indonesia.